SUMBANGAN SIBAWAYH KEPADA LINGUISTIK BAHASA ARAB: KAJIAN TERHADAP METODOLOGI PENULISAN AL-KITAB - Ali, Mohd Bakhit (Journal of Al-Tamaddun, 2009)
This article is an attempt to analyse the personality of Sibawayh, an Arabic linguistic scholar, who lived in the second century of Hijrah and his contribution to the Arabic?s linguistic in his book, al-Kitab. The debate is focused on the writing methodology of al-Kitab which had made the book well known and highly praise all over the world. The finding is expected to represent himself as the master of syntax and also as the founder of Ba?rah?s thought (madhhab)